2013
DOI: 10.1051/0004-6361/201220849
|View full text |Cite
|
Sign up to set email alerts
|

High-JCO survey of low-mass protostars observed withHerschel-HIFI

Abstract: Context. In the deeply embedded stage of star formation, protostars start to heat and disperse their surrounding cloud cores. The evolution of these sources has traditionally been traced through dust continuum spectral energy distributions (SEDs), but the use of CO excitation as an evolutionary probe has not yet been explored due to the lack of high-J CO observations. Aims. The aim is to constrain the physical characteristics (excitation, kinematics, column density) of the warm gas in low-mass protostellar env… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
134
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 77 publications
(151 citation statements)
references
References 74 publications
16
134
1
Order By: Relevance
“…In order to tackle a statistically significant source sample, the models need to be calibrated against spatially resolved observations to identify robust tracers of episodic accretion timescales. Yıldız et al (2013) compiled all available C 18 O data from J = 2-1 up to 10-9, with one omission: an integrated intensity of 11.0 K km s −1 in a 22.9 beam for the 2-1 line in Ser SMM4 (Hogerheijde et al 1999). The 6-5 and higher lines are detected in only a handful of sources and are therefore of limited use as an observational diagnostic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to tackle a statistically significant source sample, the models need to be calibrated against spatially resolved observations to identify robust tracers of episodic accretion timescales. Yıldız et al (2013) compiled all available C 18 O data from J = 2-1 up to 10-9, with one omission: an integrated intensity of 11.0 K km s −1 in a 22.9 beam for the 2-1 line in Ser SMM4 (Hogerheijde et al 1999). The 6-5 and higher lines are detected in only a handful of sources and are therefore of limited use as an observational diagnostic.…”
Section: Resultsmentioning
confidence: 99%
“…These components are also detected in various CO lines and correspond to the outflow (broad) and the quiescent envelope (narrow; Yıldız et al 2013;San José-García et al 2015). The two exceptions in our sample are L723 and B335, which only have the narrow component.…”
Section: A2 Hco +mentioning
confidence: 97%
“…As part of WISH, Kristensen et al (2010Kristensen et al ( , 2012 observed several H 2 O transitions towards the IRAS 4A source with Herschel-HIFI, showing the complex line profiles with multiple components within the HIFI beam. In the line profiles, these authors identified a broad Gaussian component (FWHM > ∼ 20 km s −1 ) that was also detected in the CO (10−9) emission (Yıldız et al 2013) and is associated with the molecular outflow. In addition, they identified a so-called medium-broad component, offset with respect to the source velocity and with smaller line widths (FWHM ∼ 5−10 km s −1 ), which they associated with currently shocked gas close to the protostar .…”
Section: Introductionmentioning
confidence: 90%
“…In this paper, we concentrate on simulating CO molecular lines of J = 2-1, 3-2, 6-5, and 9-8. For simplicity, the 12 CO abundance is set to a constant value of 10 −4 with respect to H 2 except in regions with T dust < 25 K, where it is reduced by a factor of 20 to mimic freeze-out (Jørgensen et al 2005;Yıldız et al 2013 Tobin et al 2012). For the synthetic molecular lines, the local thermal equilibrium (LTE) population levels are computed using the partition functions adopted from the HITRAN database (Rothman et al 2009).…”
Section: Observables and Radiative Transfermentioning
confidence: 99%
“…A higher excitation temperature for the gas is adopted with respect to the dust temperature following the rotational temperature derived from the observed C 18 O lines (Yıldız et al 2013). The derived masses do not depend strongly on the adopted excitation temperature.…”
Section: Disk Radii and Stellar Massesmentioning
confidence: 99%